Her Gene Family As A Therapeutic Target In Oral Squamous Cell Carcinoma - Sana Mirza; Naila Irum Hadi (ziauddin University, 2024)
Despite recent advancement in pathogenesis and management of disease, oral cancer remains the most common human malignancy, worldwide. The aggressive behavior of OSCC is a challenge for new treatment modalities for primary as well as metastatic lesions. HER receptors play an important role in the normal physiological process as well as in the development of many cancers including oral squamous cell carcinoma. An electronic article search was done through PubMed, Google Scholar and Medscape were used for an electronic search of articles, using the following keywords: oral cancer, EGFR, Her/2, Her/3 and Her /4. All types of articles were included. The aim of this review is to outline the current knowledge on the role of HER receptors in the progression of OSCC in order to use them as a therapeutic target in high risk OSCC patient and to prevent them from aggressive surgeries causing post-operative morbidity.